Edukacja emocjonalna adolescentów – program profilaktyczny ukierunkowany na wspomaganie zdrowia psychicznego - Kubiak, Hanna (Kultura-Społeczeństwo-Edukacja, 2016)
Adolescence is a time of particular susceptibility to mental disorders. A programme aimed at facilitating emotional development in teenagers might be an important element of prophylactic psychopathology targeting young people. The activities proposed here are group activities and have several aims: to develop the ability to become self-aware regarding one's emotions and regulate their intensity; to foster an attitude of caring for oneself; and to teach problem-solving. What is of particular significance is shaping young people’s habits in being proactive in their personal development.